Analisis Fungsi dan Manajemen Kawasan Konservasi Darmaloka - Andri Kurniawan (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2013)
One effort to maintain forest fungtions from futher damage is to establish and maintain conservation areas, both micro dan macro. Darmaloka conservation area in Kuningan Regency is a micro conservation area to keep preserve by functioning and managing the area. This study aimed to : (1) studying the function of Darmaloka conservation area seen from the diversity of vegetation, wildlife and water management, (2) assessing the running Darmaloka conservation area management. The study was conducted in Darmaloka corsevation area, from July to October 2010. Materials and equipment used were sketch of the area location, measuring tools, calculators, stationery, and ather supporting materials and tools. Data were collected by direct observation such as vegetation, bird, fish and water system, as well as interviews. Method of data analysis applied analysis vegetation, inventory of bird, fish density and the dischage and water quality. The results showed, there were seven types in Darmaloka conservation area, but none of them were seedlings, saplings and poles. Species Binuang (Octomeles sumatrana) dominated Darmaloka conservation areas, and the stability classified as moderate. In this area, there were 5 (five) bird species categorized rare (endangered) to medium, sacred white-Kancra fish with 5 fisher/m2 in density, catfish, and quite a lot Beunteur fish. Water discharge was about 2,94 l/sec, and the quality was good (netral). Viewed from tradition, this region well managed and controlled, but viewed from modern management, this region not regarding properly yet. It could be seen from the absence of a clear plan regarding the management of the area. The management organization was also very simple and there werenot basic clear tasks and functions amongts organization units yet.